2011
DOI: 10.1007/s10856-011-4375-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cytotoxicity of differentially sized titanium dioxide nanoparticles in murine MC3T3-E1 preosteoblasts

Abstract: There is an increased use of nanophase titanium dioxide (TiO(2)) in bone implants and scaffolds. However, nano-debris is generated at the bone-biomaterial interface. Therefore, TiO(2) nanoparticles (NPs) of many sizes were investigated for cytotoxic effects on murine MC3T3-E1 preosteoblasts. These TiO(2) NPs induced a time- and dose-dependent decrease in cell viability. There was a significant increase in lactate dehydrogenase (LDH) release, apoptosis and mitochondrial membrane permeability following short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…Superparamagnetic iron oxide nanoparticles used for stem cell tracking and magnetic resonance imaging impair the chondrogenic and osteogenic differentiation of human mesenchymal stem cells by altering the intracellular cytokine production profile of the cells, 375 and TiO 2 nanoparticles induce cytotoxicity in murine MC3T3-E1 preosteoblasts. 376 In summary, bone formation is a well-orchestrated process that involves many cell types and signaling pathways. Recent investigation has shown that nanoparticles are promising for use in bone tissue engineering.…”
Section: Nanotoxicity To Bonesmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles used for stem cell tracking and magnetic resonance imaging impair the chondrogenic and osteogenic differentiation of human mesenchymal stem cells by altering the intracellular cytokine production profile of the cells, 375 and TiO 2 nanoparticles induce cytotoxicity in murine MC3T3-E1 preosteoblasts. 376 In summary, bone formation is a well-orchestrated process that involves many cell types and signaling pathways. Recent investigation has shown that nanoparticles are promising for use in bone tissue engineering.…”
Section: Nanotoxicity To Bonesmentioning
confidence: 99%
“…For example, TiO 2 NPs could induce DNA double-strand breaks in bone-marrow cells after oral administration. 4 Zhang et al 5 observed that TiO 2 NPs stimulated pro-inflammatory gene expression in pro-osteoblast cells (MC3T3-E1). Wang et al 6 indicated that TiO 2 NPs are potentially toxic to major organs and cause damage to the knee joints in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, hydroxyapatite and titania nanoparticles of up to 40 nm diameter decreased osteoblastic cell proliferation and viability, respectively. 99,116 On the other hand, in another study, only hydroxyapatite nanoparticles with a diameter of 20 nm enhanced cell growth of osteoblast-like cells compared with larger particles with a diameter of 80 nm. 117 In addition to particle uptake by osteoblasts and potential effects on proliferation and viability, the consequences of nanoparticle presence on the differentiation and mineralization of osteoblastic cells were assessed in a variety of studies with a wide range of particles.…”
Section: Osteoblastsmentioning
confidence: 92%
“…123 Similar osteoclastogenic effects were triggered in osteoblastic cells by titania nanoparticles via increased gene expression of granulocyte colony-stimulating factor. 116 In contrast, phosphonate-functionalized nanoparticles did not affect the expression of osteoclast-regulating genes in primary human osteoblasts. 112 Further examined effects of nanoparticles on osteoblasts comprised DNA damage, confirmed for hydroxyapatite nanoparticles in osteoblastic cells, 115 and titania particles in various murine organs, including bone marrow.…”
Section: Osteoblastsmentioning
confidence: 95%
See 1 more Smart Citation